2011
DOI: 10.1073/pnas.1019593108
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli sister chromosome separation includes an abrupt global transition with concomitant release of late-splitting intersister snaps

Abstract: The basis for segregation of sister chromosomes in bacteria is not established. We show here that two discrete~150-kb regions, both located early in the right replichore, exhibit prolonged juxtaposition of sister loci, for 20 and 30 min, respectively, after replication. Flanking regions, meanwhile, separate. Thus, the two identified regions comprise specialized late-splitting intersister connections or snaps. Sister snap loci separate simultaneously in both snap regions, concomitant with a major global nucleoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

16
178
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 110 publications
(194 citation statements)
references
References 31 publications
16
178
0
Order By: Relevance
“…Such effects were first reported by Fisher and co-workers 13,16 , who, for example, observed that the splitting of the gln locus is accompanied by rapid, asymmetric separation of sister loci, indicating that the basis for the movement is accumulated stress within the nucleoid. More recently, they proposed that programmed intranucleoid 'tethers' (for example, by nucleoidassociated bridging proteins like H-NS or Fis, or by condensins like MukB), accumulate in inter-segment linkages, which, in combination with changes in supercoiling state, tend to put the chromosome in an unfavourable condition, promoting eventual catastrophic release of tethers.…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…Such effects were first reported by Fisher and co-workers 13,16 , who, for example, observed that the splitting of the gln locus is accompanied by rapid, asymmetric separation of sister loci, indicating that the basis for the movement is accumulated stress within the nucleoid. More recently, they proposed that programmed intranucleoid 'tethers' (for example, by nucleoidassociated bridging proteins like H-NS or Fis, or by condensins like MukB), accumulate in inter-segment linkages, which, in combination with changes in supercoiling state, tend to put the chromosome in an unfavourable condition, promoting eventual catastrophic release of tethers.…”
Section: Discussionmentioning
confidence: 87%
“…Additionally, such global rearrangements are expected to also affect loci that are not within the main moving domains. Considering the average trajectories of the 1-min frame separation data, we did not find direct evidence of the discrete transitions in the cell cycle 13,16 , likely because our technique, . Cells were imaged and segmented every minute, in order to reconstruct the segregation cycle, and the data were synchronized by the time at which the replicated sister loci were resolved optically (origin of times in these plots).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations